2020
DOI: 10.1038/s41598-020-77431-1
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the pharmacological mechanism of the effects of the Banxia-Xiakucao Chinese Herb Pair on sleep disorder by a systems pharmacology approach

Abstract: Sleep disorder (SD) has a high incidence and seriously affects quality of life, mental health and even the manifestation of physical diseases. The combination of Pinellia ternata (Chinese name: banxia) and Prunella vulgaris (Chinese name: xiakucao), known as the Banxia–Xiakucao Chinese herb pair (BXHP), is a proven Chinese herbal medicine that has been used to treat SD for thousands of years due to its significant clinical effects. However, its active pharmacological components and sedative–hypnotic mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Inhibition of PDK3 activity or expression levels increases mitoROS, oxidative phosphorylation, and pyruvate dehydrogenase activity under normoxic conditions ( Kluza et al, 2012 ). Other pharmacology and molecular docking analyses have revealed that P. vulgaris (in both plant and prepared medicine forms) affects HIF-1α and the apoptosis signaling pathway in sleep disorders ( Guo et al, 2020 ), thyroiditis ( Shen et al, 2020 ), and diabetes mellitus ( Jiao et al, 2021 ). Moreover, UA and its derivatives have been trialed as HIF-1α inhibitors with anticancer potential ( Shan et al, 2016 ; Wang et al, 2016 ; Chi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of PDK3 activity or expression levels increases mitoROS, oxidative phosphorylation, and pyruvate dehydrogenase activity under normoxic conditions ( Kluza et al, 2012 ). Other pharmacology and molecular docking analyses have revealed that P. vulgaris (in both plant and prepared medicine forms) affects HIF-1α and the apoptosis signaling pathway in sleep disorders ( Guo et al, 2020 ), thyroiditis ( Shen et al, 2020 ), and diabetes mellitus ( Jiao et al, 2021 ). Moreover, UA and its derivatives have been trialed as HIF-1α inhibitors with anticancer potential ( Shan et al, 2016 ; Wang et al, 2016 ; Chi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [ 58 ] showed that SXD exhibited beneficial sedative and hypnotic bioactivity by modulating serotoninergic function and the immune system. Guo et al [ 59 ] performed systematic pharmacological research and found that SXD could treat sleep disorders by reducing inflammatory responses and regulating the immune and central nervous systems. Zhong et al [ 60 ] found that the essential oil of ZS potentially exerted sedative and hypnotic effects by regulating the GABAergic system pathway in mice with PCPA-induced insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Salah satunya yaitu terkait aktivitas sedatif-hipnotik. Tumbuhan memiliki kemampuan sedatif hipnotik karena mengandung senyawa d-limonen, linalool, linalil asetat, santalol, kaemferol, luteolin, b-sitosterol, stigmasterol, dan baicalein (Guo et al 2020;Zhong et al 2019). Beberapa senyawa tersebut juga terdapat dalam daun keji beling (Strobilanthes crispus L.) dan telah dibuktikan oleh (Inayah et al, 2021) secara in-silico dengan metode molecular docking bahwa kandungan d-limonen dalam daun keji beling merupakan senyawa yang paling berpotensi sebagai sedatif hipnotik karena memiliki nilai energi ikatan sebesar (-4,2 kkal/mol) mendekati nilai energi ikatan dengan ligan alami reseptor GABA (-4,3 kkal/mol) dan benzodiazepin sebagai kontrol positif (-4,4 kkal/mol).…”
Section: Pendahuluanunclassified